A Hybrid Learning Approach for Subjects on Software Development of Automation Systems, Combining PBL, Gamification and Virtual Reality - Leite, Dênis; Santos, Higor; Rodrigues, Ariane; Monteiro, Cléviton; Maciel, Alexandre (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2021)
Despite the practical classes in laboratories and simulations, the traditional automation engineering teaching and learning process remains with little adherence to the reality professional. In this context, this research proposes a hybrid teaching and learning approach for subjects on software development of automation systems based on problems with virtual reality features and gamification strategies. Its main objective is to enhance the alignment between theory and practice, playfully and engagingly mirrored in the industry's need. The proposed approach was developed based on Design Science Research and evaluated in seven classes of an undergraduate subject from the perspective of students and industrial professionals. The results evidence the evolution of the approach over the time and the ability to promote the connection between theory and professional practice.